Hubungan posisi kerja duduk dengan tingkat disabilitas nyeri punggung bawah pada pengrajin purun di Kabupaten Katingan - Junanda, Rizky Ari Sandy; Tori, Marthin; Komara, Nisa Kartika; Arifin, Syamsul; Surbakti, Ranintha Br (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Low back pain is a sensation of pain in the lumbosacral area in the form of local pain, radicular pain, or a combination of both pains. Low back pain is divided, acute and chronic. Factors that can cause lower back pain include age, obesity, work position, work period and workload. Work ergonomic factors include monotonous and uncomfortable work postures with heavy loads and lasting for long periods of time. Identifying the characteristics of sitting working positions and lower back pain among purun craftsmen in Katingan Hilir and Malan Island Districts. This research uses analytical observational with a cross-sectional design. Sampling used total sampling technique with a total of 39 respondents. Using the REBA and ODI questionnaires. Bivariate data analysis using Spearman. The results of the Spearman test obtained a significance value of p=0.021 (p<0.05) with a correlation coefficient value of (r=-0.369) with a unidirectional relationship. There is a relationship between sitting working position and the level of lower back pain disability in purun craftsmen in Katingan Hilir and Malan Island Districts, Katingan Regency, Central Kalimantan.